1987
DOI: 10.1210/endo-120-6-2272
|View full text |Cite
|
Sign up to set email alerts
|

Greaterin Vivothan in Vitro Pulsatility of Insulin Secretion with Synchronized Insulin and Somatostatin Secretory Pulses

Abstract: To examine the control of pulsatile insulin secretion by an intrapancreatic pacemaker, samples at minute intervals were taken from the portal vein in dogs in vivo and from an isolated perfused pancreas preparation in vitro. Anesthetized dogs had high amplitude pulsatile insulin secretion which was not consistently regular. Fourier transform analysis showed dominant 20- and 10-min periods of spectral power (P less than 0.01). After vagotomy, the relative oscillatory power was reduced from 83% to 42%, about a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…The high frequency sampling and replicate measurements are costly so sampling duration should be short. The repetitive nature of pulsatile insulin secretion [4,5,10,33,76] would allow a reliable measurement of pulse frequency and amplitude using a sampling duration of 40 to 60 min [69] if deconvolution analysis or simple pulse detection algorithms are used. However, analysis based on autocorrelation (minimum 2 times pulse interval) and on spectral analysis (n > 100) as well as regularity statistics (approximate entropy: n > 40) in general improve with increased sampling duration and therefore most studies using periodicity statistics are carried out over a longer duration [4,5,10,33,76].…”
Section: Methods For Assessing Pulsatile Insulin Secretionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high frequency sampling and replicate measurements are costly so sampling duration should be short. The repetitive nature of pulsatile insulin secretion [4,5,10,33,76] would allow a reliable measurement of pulse frequency and amplitude using a sampling duration of 40 to 60 min [69] if deconvolution analysis or simple pulse detection algorithms are used. However, analysis based on autocorrelation (minimum 2 times pulse interval) and on spectral analysis (n > 100) as well as regularity statistics (approximate entropy: n > 40) in general improve with increased sampling duration and therefore most studies using periodicity statistics are carried out over a longer duration [4,5,10,33,76].…”
Section: Methods For Assessing Pulsatile Insulin Secretionmentioning
confidence: 99%
“…However, the net contribution of the secretory bursts is important, because the presence of concentration oscillations does not exclude the dominance of a time-invariant (basal) release pattern. Furthermore, the relation between the in vivo observed secretory bursts and the in vitro observed pulsatile release from the isolated pancreas [9,10,101] and the isolated peri-perfused islets [102,103], as well as episodic beta-cell depolarization [104±106], beta-cell glycolysis [105,107], and beta-cell increase in calcium remains to be established [104, 105, 108±111]. The coupling of cyclic metabolism to pulsatile in vitro release has been addressed in an excellent review by Tornheim [112].…”
Section: Contribution Of Pulsatile Insulin Release To the Overall Insmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in normal subjects with suppressed endogenous insulin secretion and diabetic patients have indicated that less insulin is required to maintain normoglycaemia if the hormone is infused in an oscillatory manner compared to a constant rate (Matthews et al, 1983b;Bratusch-Marrain et al, 1986;Matthews et al, 1987;Paolisso et al, 1988a;Paolisso et al, 1988b). The better efficiency of oscillatory insulin delivery is probably due to higher expression of insulin receptors (Goodner et al, 1988).…”
mentioning
confidence: 99%
“…Most studies are time and cost consuming, and the ideal sampling duration should be the shortest duration to give reliable data. With deconvolution analysis and pulse detection analysis, 40 -60 min (64) seems to result in good data whereas regularity statistics (autocorrelation [minimum two times pulse interval] and spectral analysis [N Ͼ100]) as well as regularity statistics (approximate entropy: N Ͼ40) improve with increased sampling duration (5,6,9,26,67). Insulin versus C-peptide measurements.…”
mentioning
confidence: 99%